The defence lawyering strategy of a defence counsel ‘Maestro’: Lawyers and legal reasoning in authoritarian regimes - Fijalkowski, Agata (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2026)
An analysis of the life account of the Polish defence lawyer Stanisław Hejmowski (1900–1969), who made a mark in the first national war crimes trial in 1946 and later in the Poznań June trials of 1956, reminds us of how defence lawyering strategies in high profile cases are born. This paper’s findings draw on his recently discovered private personal archive and case notes, which have hitherto not been in the public domain. The investigation shows that Hejmowski’s line of action exemplifies a strategy through which a civil lawyer may approach large-scale atrocities and crimes – but as a criminal defence lawyer. Through this analysis and a consideration of an unconventional figure we may hope to appreciate what legal reasoning signifies in authoritarian states.